2006
DOI: 10.1111/j.1365-2109.2006.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Panagrellus redivivus mass produced on solid media as live food for Litopenaeus vannamei larvae

Abstract: The free‐living soil nematode Panagrellus redivivus is well known to be an excellent food source for first feeding fish larvae. It represents an alternative to the highly expensive Artemia, which is commonly used. The lack of a proper method for mass production of P. redivivus has prevented its wider use in commercial hatcheries. A new cultivation method allows the production of a sufficient quantity of nematodes to deliver a standardized and permanently available live food of high quality, throughout the larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 24 publications
(53 reference statements)
3
28
2
3
Order By: Relevance
“…Biedenbach et al (1989) raised Pacific white shrimp (Litopenaeus vannamei) larvae on nematodes and showed that the larvae fed with different nematode densities grew faster or were at least similar in comparison to an Artemia diet. Also in Pacific white shrimp larvae, Focken et al (2006) showed that there was little difference in survival when fed either nematodes or Artemia and that larvae grew almost as fast as with Artemia in high enough nematode densities (100-150 Ind. ml À1 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Biedenbach et al (1989) raised Pacific white shrimp (Litopenaeus vannamei) larvae on nematodes and showed that the larvae fed with different nematode densities grew faster or were at least similar in comparison to an Artemia diet. Also in Pacific white shrimp larvae, Focken et al (2006) showed that there was little difference in survival when fed either nematodes or Artemia and that larvae grew almost as fast as with Artemia in high enough nematode densities (100-150 Ind. ml À1 ).…”
Section: Introductionmentioning
confidence: 97%
“…Also in Pacific white shrimp larvae, Focken et al. () showed that there was little difference in survival when fed either nematodes or Artemia and that larvae grew almost as fast as with Artemia in high enough nematode densities (100–150 Ind. ml −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zoeal stages feed mainly on phytoplankton (3-30 lm diameter) by filter-feeding, although from stage Z2, depending on the penaeid species, they can capture animal prey of up to 100 lm raptorially (Jones, Kumlu, Le Vay & Fletcher 1997). Feeding on animal organism as early as Z2 has been documented by several authors, using rotifers (Emmerson 1984;Samocha et al 1989;Naessens, Cobo, Van Hauwaert, Van Horenbeeck & Sorgeloos 1995), nematodes (Wilkenfeld 1984;Biedenbach, Smith, Thomsen & Lawrence 1989;Focken, Schlechtriem, von Wuthenau, Garc ıa-Ortega, Puello-Cruz & Becker 2006), copepods (D'Abramo et al 2006) and Artemia nauplii in different forms such as live freshly-hatched nauplii (Kuban, Lawrence & Wilkenfeld 1985;Samocha et al 1989;Lavens & Sorgeloos 1996) and frozen nauplii (Wilkenfeld, Fox & Lawrence 1981). Some commercial hatcheries start feeding Instar 1 Artemia nauplii as early as possible, because a number of studies have documented the benefit of an introduction of an animal protein source in the zoea stages (Wilkenfeld 1984;Samocha et al 1989;Naessens et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding on animal organism as early as Z2 has been documented by several authors, using rotifers (Emmerson ; Samocha et al . ; Naessens, Cobo, Van Hauwaert, Van Horenbeeck & Sorgeloos ), nematodes (Wilkenfeld ; Biedenbach, Smith, Thomsen & Lawrence ; Focken, Schlechtriem, von Wuthenau, García‐Ortega, Puello‐Cruz & Becker ), copepods (D'Abramo et al . ) and Artemia nauplii in different forms such as live freshly‐hatched nauplii (Kuban, Lawrence & Wilkenfeld ; Samocha et al .…”
Section: Introductionmentioning
confidence: 99%
“…Panagrolaimidae, 'microworms') are commonly used as food for ornamental fish larvae and have been positively tested as larval food in aquaculture fish as well as crustacean species (e.g. Biedenbach et al, 1989;Rottmann et al, 1991;Santiago et al, 2003Santiago et al, , 2004Focken et al, 2006;Sautter et al, 2007). Due to their size, shape and active movement, nematodes are a suitable prey item for fish and crustacean larvae.…”
Section: Introductionmentioning
confidence: 99%